2020
DOI: 10.1016/j.arr.2019.101005
|View full text |Cite
|
Sign up to set email alerts
|

Education and age-related decline in cognitive performance: Systematic review and meta-analysis of longitudinal cohort studies

Abstract: Association of education and change in cognitive performance is negligible.• Articles included in meta-analysis displayed high unexplained heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
83
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 89 publications
17
83
3
Order By: Relevance
“…However, studies that have attempted to address this issue have not reported substantially altered estimates (Foverskov et al, 2018;Glymour et al, 2012;Gottesman et al, 2014). We also note that in the meta-analysis described above, estimates of the association between educational attainment and cognitive change were related neither to participants' age nor to the length of follow-up (Seblova et al, 2020). Given that age and length of follow-up would likely be associated with the extent of a bias introduced by selective dropout, these results do not suggest that selective dropout had a major influence on the estimates.…”
Section: Education and Aging-related Cognitive Changes In The Generalmentioning
confidence: 82%
See 3 more Smart Citations
“…However, studies that have attempted to address this issue have not reported substantially altered estimates (Foverskov et al, 2018;Glymour et al, 2012;Gottesman et al, 2014). We also note that in the meta-analysis described above, estimates of the association between educational attainment and cognitive change were related neither to participants' age nor to the length of follow-up (Seblova et al, 2020). Given that age and length of follow-up would likely be associated with the extent of a bias introduced by selective dropout, these results do not suggest that selective dropout had a major influence on the estimates.…”
Section: Education and Aging-related Cognitive Changes In The Generalmentioning
confidence: 82%
“…Most previous studies have focused on older age, and it may, for example, be the case that an association is present during early adulthood. However, the reviewed meta-analysis (Seblova et al, 2020) and recent studies including an adult life-span sample (participants were 35-80 years old) have shown no strong indication that effects of education on cognitive ability are larger at younger ages (Berggren et al, 2018). It may also be that an association is nonlinear, such that effects of educational attainment on cognitive change may appear, for example, in samples of individuals who are poorly educated, but no such pattern was evident for any cognitive outcome examined in the reviewed meta-analysis.…”
Section: Education and Aging-related Cognitive Changes In The Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well-established that there is a positive association between education and various cognitive functions, including memory, attention, and executive function in healthy older adults (Cabral et al, 2016;Opdebeeck et al, 2016;Zhang et al, 2019). However, other studies have also reported that education is associated with the level of cognitive performance in healthy older adults but not with the rate of cognitive decline itself (Bendayan et al, 2017;Seblova et al, 2020). Our result also showed little association between working activity and detailed neuropsychological tests in both correlation and regression analyses, implying little effect of working activities on detailed cognition at the early stage of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%